Adoption of cryptocurrencies in developing countries - Rajmon, Ondřej; Jedlinský, Jakub; Šaroch, Stanislav, 1970-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The thesis scrutinizes crypto adoption with particular concern for developing countries. Based on preliminary research, we identified the following factors indicating an influence on crypto adoption: GNI per capita, business freedom, government effectiveness, corruption control, political stability, history of inflation, and tax burden. The effect of these variables was analyzed using correlation and linear regression. Specifically, two regression models were performed to explain dependent variables – the crypto adoption index and P2P exchange trade volumes. The results suggest a statistically significant relationship between the variables and the crypto adoption index, while the effect was insignificant for business freedom and corruption control in the case of P2P exchange trade volumes. An exchange trade volume gap between developed and developing countries was detected, indicating that developing countries utilize cryptocurrencies as a means of exchange significantly more. Finally, we conclude that crypto adoption is prevalent in countries having a crypto regulation in place, a certain level of functioning public services and infrastructure, corrupt and politically unstable governments, an experience with high inflation, and that levies higher taxes.
Vedoucí práce: Jakub Jedlinský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: evropská ekonomická integrace [obor dipl. práce]; diplomové práce; master's theses